Pengaruh Metode Cerita Berseri terhadap Peningkatan Kosakata Anak Usia 5-6 Tahun di TK Mandiri ABCD Sipoholon - Resteulina Zaluhu; Adiani Hulu; Emmi Silvia Herlina (Institut Nalanda, 2024)
The aim of this research is to determine the effect of the serial story method on increasing the vocabulary of early childhood at the ABCD Sipoholon Mandiri Kindergarten. The method used in this research is a quantitative research method with descriptive statistics. The population was all children at the Mandiri ABCD Sipoholon Kindergarten, totaling 108 people and a sample of 20 children was determined. Data was collected using an observation sheet of 30 items. The result of data analysis show that there is an influence of the serial story method on increasing the vocabulary of early childhood at the ABCD Sipoholon Mandiri Kindergarten : 1) Test analysis requirements: a) Positive relationship test obtained by the value rxy = 0.658 > rtable( a=0.05,n=20) = 0.444, thus it is know that there is a positive relationship between variabel X and variabel Y. b) a significant relationship test was obtained thitung=3,711>ttabel(α=0,05,dk=n-2=18)= 2,101 thus there is a significant relationship between variabel X and variabel Y. c) regression coefficient of determination test (r2)=43,3%. 2) influence test: regression equation test, the regression equation is obtained . Thus Ha is accepted and Ho is rejected.